2016
DOI: 10.1007/s10858-016-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards interpretation of intermolecular paramagnetic relaxation enhancement outside the fast exchange limit

Abstract: In an exchanging system between major and minor species, the transverse paramagnetic relaxation enhancement rate observed on the resonances of the major species (Γ 2 (app) ) is dependent upon the exchange regime between the species. Quantitative analysis of PRE data in such systems typically assumes that the overall exchange rate k ex between the species is fast on the PRE time scale (k ex ≫ Γ2). Recently, we have characterized the kinetics of binding of the model protein ubiquitin to large (LUV) and small (SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recent studies demonstrated the possibility of obtaining high‐resolution detail of nano‐bio interfaces . It emerged that simple protein molecules could be adsorbed on NPs at specific binding sites, in analogy with the mode of recognition of natural protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the possibility of obtaining high‐resolution detail of nano‐bio interfaces . It emerged that simple protein molecules could be adsorbed on NPs at specific binding sites, in analogy with the mode of recognition of natural protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to preserve the robustness of analysis for all domains and linkage types of Ub 2 and to enable direct comparison of the dynamics parameters obtained for different Ub 2 domains, we chose to determine the values of k on app,LUV for the different Ub 2 –LUV interactions independently from paramagnetic relaxation enhancement (PRE) experiments (Figure ). Outside the fast exchange regime ( k ex < Γ 2 , where Γ 2 is the PRE rate in the bound species), the maximal observed PRE, 1 H N –Γ 2,max app , after background subtraction, approaches a limiting value that is a factor of ∼1.3 lower than k on app,LUV for the exchange parameters previously established for Ub 1 . The values of k on app,LUV thus estimated from 1 H N –Γ 2,max app for each Ub 2 domain are reported in the first row of Table , which summarizes the parameters of exchange and dynamics obtained by combined analysis of LUV and SUV Δ R 2 data for the distal/proximal domains of K63- and K48-linked Ub 2 .…”
mentioning
confidence: 96%
“…Therefore, to preserve the robustness of analysis for all domains and linkage types of Ub 2 and to enable direct comparison of the dynamics parameters obtained for different Ub 2 domains, we chose to determine the values of k on app,LUV for the different Ub 2 − LUV interactions independently from paramagnetic relaxation enhancement (PRE) experiments (Figure 2). 16 Outside the fast exchange regime (k ex < Γ 2 , where Γ 2 is the PRE rate in the The PRE background, due to diffusion of Ub 2 in the magnetic field generated by Gd 3+ -tagged LUVs, 3 is shown as a dashed line. The most significant PREs above background are shaded in gray.…”
mentioning
confidence: 99%
See 1 more Smart Citation